2019
DOI: 10.1093/mnras/stz1388
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inhomogeneous reionization on the Lyman-α forest

Abstract: The Lyman-α forest at high redshifts is a powerful probe of reionization. Modeling and observing this imprint comes with significant technical challenges: inhomogeneous reionization must be taken into account while simultaneously being able to resolve the web-like small-scale structure prior to reionization. In this work we quantify the impact of inhomogeneous reionization on the Lyman-α forest at lower redshifts (2 < z < 4), where upcoming surveys such as DESI will enable precision measurements of the flux po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 86 publications
2
33
0
Order By: Relevance
“…On even larger scales still, the clustering of the ionizing sources and the size of the ionized bubbles during reionization leave their imprints on the Lyα flux via temperature fluctuations. A number of works have shown that large-scale correlations in the IGM temperature field can bring excess power in the lowest observable wavenumbers in the power spectrum (Cen et al 2009;D'Aloisio et al 2018;Oñorbe et al 2019;Montero-Camacho et al 2019), but the small-scale effects of temperature fluctuations have still not been studied in detail.…”
mentioning
confidence: 99%
“…On even larger scales still, the clustering of the ionizing sources and the size of the ionized bubbles during reionization leave their imprints on the Lyα flux via temperature fluctuations. A number of works have shown that large-scale correlations in the IGM temperature field can bring excess power in the lowest observable wavenumbers in the power spectrum (Cen et al 2009;D'Aloisio et al 2018;Oñorbe et al 2019;Montero-Camacho et al 2019), but the small-scale effects of temperature fluctuations have still not been studied in detail.…”
mentioning
confidence: 99%
“…Using the same high-resolution simulations, Montero-Camacho et al (2019) reported for the first time the impact of inhomogeneous reionization in the Ly𝛼 forest 3D and 1D power spectrum at lower redshifts 1 . The expected effect of the memory of inhomogeneous reionization in terms of the relative difference is currently estimated to range from six per cent at 𝑧 = 2 up to fifty per cent at 𝑧 = 4 for the 3D Ly𝛼 power spectrum, and it ranges from a per cent at 𝑧 = 2 up to roughly twenty per cent at 𝑧 = 4 for the 1D power spectrum (Montero-Camacho & Mao 2020; hereafter "MM20").…”
Section: Introductionmentioning
confidence: 94%
“…(1) Small-scale simulations: we utilize the modified Gadget2 (Springel 2005) simulations described and tested in detail in Hirata 1 The 1D results in Montero-Camacho et al (2019) were compromised by an error in their mapping from 3D to 1D that was later corrected in Montero-Camacho & Mao (2020). (2018).…”
Section: Simulations and Forecast Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Cen et al 2009;Keating et al 2018;D'Aloisio et al 2019) or semi-numerical reionisation models (e.g. Lidz & Malloy 2014;Montero-Camacho et al 2019), these neglect the dynamical effect of patchy heating on the small scale structure of the Ly𝛼 forest (i.e. the scales at wavenumbers 𝑘 ∼ 0.1 km −1 s that are most sensitive to the IGM thermal state and the coldness of dark matter at 𝑧 > 4).…”
Section: Introductionmentioning
confidence: 99%